Social and structural determinants associated with the prevalence of sexually transmitted infections among female commercial sex workers in Dhaka City, Bangladesh. - Mahbuba Kawser; Md Nazrul Islam Khan; Kazi Jahangir Hossain; Sheikh Nazrul Islam (Public Library of Science (PLoS), 2024)
Female commercial sex workers (FCSWs) bear higher rates of sexually transmitted infections (STIs) among key populations. The association of structural determinants and STIs among FCSWs was not at the forefront of research earlier in Bangladesh. This study examined how structural factors correlate with the prevalence of STIs at physical/social/economic/policy levels among FCSWs in Dhaka city. 495 FCSWs were screened for HIV, hepatitis B, and syphilis. Structural variables (Individual risks, high-risk sexual behaviors, work environments) were extracted from the previous multi-level study on FCSWs and analyzed in 2020 to determine whether macro/micro-structural factors were associated with STIs. The prevalence of STIs was 43.6% (95% CI: 39.1%-48). Most (n = 207/495) FCSWs were infected with Syphilis or Hepatitis B, only 1.8% had co-infection, and none was positive for HIV. Multiple logistic regression revealed that 'Individual risk' factors like age (≤18 years, adjusted odds ratio = AOR = .28; 18.1-29.9 years, AOR = .57), years in the sex industry (<1 year AOR = .15; 1-5 years, AOR = .39), and condoms as contraceptives (AOR = 2.7) were significantly associated with STIs. Considering 'High-risk behaviors' like monthly coitus with regular clients (AOR = .33), performing no anal sex ever (AOR = .03), and consistent condom use (AOR = .13) were less likely to be associated with STIs (P<0.05), while the association of ever group sex with STIs reported to double (AOR = 2.1). 'Work environment' like sex on roads/parks/shrines/markets (AOR = 2.6) and ever HIV-testing (AOR = 2.5) were significantly linked with STIs. However, micro-level factors like experiencing forced sex in the past year (AOR = 1.79) and condoms collected from hotel boys (AOR = .34) were significantly associated with STIs in the 'Hierarchical- model' with increasing model-power. 'Micro-structural' determinants predominated over 'Macro/policy-level factors' and profoundly influenced STIs. FCSWs need comprehensive and integrated interventions to promote accurate condom use perception, eliminate risky sexual behaviors, and provide quality reproductive health care. Necessary steps at the policy level are urgently needed to decriminalize commercial sex work.